2013
DOI: 10.1386/jfs.1.2.201_1
|View full text |Cite
|
Sign up to set email alerts
|

‘I’m not a lawyer but …’: Fan disclaimers and claims against copyright law

Abstract: Fan fiction has become increasingly widespread, and online discussions between fans about fan fiction and copyright reveal the extent to which fans are both governed by and resist copyright law, as they understand it. As complex agents both within and outside of law, writers and supporters of fan fiction reveal the problems of speaking against law from a position that is regulated by law, a position creative re-producers are forced to occupy in an increasingly copyrighted, patented and trademarked world. So lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…For example, conflicts that have erupted over the years in fan communities reveal a number of strongly entrenched social norms related to copyright: norms about plagiarism, attribution, what constitutes commercialization, and "filing the serial numbers" off fan fiction (i.e., changing the names of characters and then publishing it) [21]. Remixers such as fan fiction writers represent a group struggling to understand and locate the law within these cultural norms [29]. In some communities, these norms and ethical standards have been formalized into codes of best practices [2].…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, conflicts that have erupted over the years in fan communities reveal a number of strongly entrenched social norms related to copyright: norms about plagiarism, attribution, what constitutes commercialization, and "filing the serial numbers" off fan fiction (i.e., changing the names of characters and then publishing it) [21]. Remixers such as fan fiction writers represent a group struggling to understand and locate the law within these cultural norms [29]. In some communities, these norms and ethical standards have been formalized into codes of best practices [2].…”
Section: Related Workmentioning
confidence: 99%
“…However, even without the knowledge to back it up, intricate intuitions about the law can form, which we have specifically seen in communities of online content creators [13,14,27,28,29].…”
Section: Related Workmentioning
confidence: 99%
“…Bacon-Smith (1992: 45) argues that fans create texts for personal and subcultural community enjoyment rather than public circulation and, as a result, subcultural community approval is important (also see Jenkins, 1988). Though homogeneity and consensus cannot be guaranteed within any community, fanfic communities centred around high-profile source material are particularly careful to avoid any suggestion of legal culpability (see Roth and Flegel, 2013). Ethnographic studies have shown that creation of environments and knowledge spaces where fans can interact with others is an important aspect of fandom (Scodari, 2003;Scodari and Felder, 2000).…”
Section: '[W]orlds Apart': the Histories Of Fifty Shades Of Greymentioning
confidence: 99%